2020
DOI: 10.21203/rs.3.rs-25876/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplementation with sodium butyrate improves growth and antioxidant function in dairy calves before weaning

Abstract: Background: There is increasing research interest in using short-chain fatty acids (SCFAs) including butyrate as potential alternatives to antibiotic growth promoters in animal production. This study was conducted to evaluate the effects of supplementation of sodium butyrate (SB) in milk and/or milk replacer on the growth performance, rumen fermentation, and serum antioxidant capacity and immunoglobins in dairy calves before weaning. Forty healthy female Holstein calves (4-day-old; 40 ± 5 kg of body weight) we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…These data suggested that SB administration effectively augmented the antioxidant defense system of the intestine. These results are consistent with Liu et al [46] who showed that SB improves antioxidant function in dairy calves before weaning.…”
Section: Discussionsupporting
confidence: 93%
“…These data suggested that SB administration effectively augmented the antioxidant defense system of the intestine. These results are consistent with Liu et al [46] who showed that SB improves antioxidant function in dairy calves before weaning.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, supplementation with FA2 increased serum IgM concentration on d 28, which is consistent with the previous study [2625,2726]. However, Liu et al found that dietary sodium butyrate did not affect the serum concentrations of any of the 3 antibodies of calves [21], this may be due to the animal species used or methods of butyrate supplementation. Moreover, studies in vivo and ex vivo found that antimicrobial action of MCFA on E. coli and the improvement of MCFA on IgA in piglets [2827].…”
Section: Discussionsupporting
confidence: 91%
“…Zhang et al reported that dietary sodium butyrate decreased MDA concentration and increased SOD activity of serum in chicken [20]. Furthermore, dietary supplementation of sodium butyrate was shown to increase GSH-Px activity and decrease MDA concentration in pre-weaned A c c e p t e d A r t i c l e dairy calves [21]. In general, these results all showed that butyrate could improve antioxidant ability in animals.…”
Section: Discussionmentioning
confidence: 89%
“…In total, 45 2-month-old male Sprague-Dawley rats were fed adaptively during the first week, weighed, numbered and randomly divided into three groups. Randomization was performed using the 'RAND' function on Microsoft Excel (Microsoft Corporation) 2016 (18). Ultimately, 45 animals were assigned to each of the three following groups: Normal group (n=15), model group (n=15) and the ABPS group (n=15).…”
Section: Mainmentioning
confidence: 99%